Installation Art and the Museum Presentation and Conservation of Changing Artworks - van Saaze, Vivian (Amsterdam University Press, 2013)
Installation art has become mainstream in artistic practices. However, acquiring and displaying such artworks implies that curators and conservators are challenged to deal with obsolete technologies, ephemeral materials and other issues concerning care and management of these artworks. By analysing three in-depth case studies, the author sheds new light on the key concepts of traditional conservation (authenticity, artist's intention, and the notion of ownership) while exploring how these concepts apply in contemporary art conservation. Based on original empirical research and cross-case analysis, this ground-breaking study offers a re-examination of traditional conservation values and ethics, and argues for a reassessment of the role of the conservator of contemporary art.